Institutional diagnostics for African food security: Approaches, methods and implications. (1st March 2018) - Schouten, Greetje; Vink, Martinus; Vellema, Sietze
Highlights: Diagnostics of institutional contexts enhances understanding food security in Africa. Ex-ante institutional diagnostics is necessary before considering possible interventions. Institutional diagnostics guides the design of locally appropriate interventions. Institutional diagnostics is advanced by systematically triangulation theories. Institutional diagnostics implies crossing (trans)disciplinary boundaries. Abstract: Securing access to affordable and nutritious food is an urgent topic on the agenda for development strategies in Africa. Intervention strategies targeting food security triggered a long lasting debate whether science and technology driven interventions could be the panacea for hunger eradication. However, contextual factors are extremely important in determining food security, as it is a location specific outcome of how biophysical, geographical, societal and political factors combine. Recent studies emphasize the important role of institutions to understand the persistence of food insecurity or to explain how different actors address food security. This article introduces a special issue that investigates approaches and methods, anchored in different institutionalisms, diagnosing how institutions influence food security levels in diverse African contexts. We draw two main lessons from this special issue. Firstly, there is a clear need for localized ex-ante institutional diagnostics to understand developments in food security in Africa. This can inform and guide decision-makers in designing locally appropriate interventions. Secondly, developing institutional diagnostics in view of sustainable food security requires theoretical triangulation; food insecurity is typically a problem emerging from a configuration of distinct processes. To develop a contextual and precise understanding of how institutions work and to identify what an institutional context 'is good at', the special issue argues in favour of an interdisciplinary approach in the social sciences that is strongly rooted in evolving practices (re)arranging institutions affecting food security.